La progressiva evoluzione della procedura di rilascio delle concessioni demaniali marittime in una dimensione eurounitaria tra accelerazioni giurisprudenziali e rallentamenti normativi - Stile, Maria Teresa (Diritto Pubblico Europeo - Rassegna online, 2023)
The regulatory framework of state maritime concessions for tourist-recreational purposes, after a long period of static nature, has been the subject, in the last period, of a sudden transition from the principles envisaged by the dating back rules of the navigation code to the European-derived principles of competition and the free movement of services. The legislative intervention to reorganize the matter, started by the twin sentences of the Council of State in 2021 and continued with the sentence of the Court of Justice in 2023, has not yet been completed, requiring the exercise of the executive discretion power, on "scarcity of the resource", carried out through an investigation of technical consultative body. The Government’s position, with the Report on the progress of the Technical Consultative Table’s work, unbalanced the relationship between administrative and European justice and national policy, replacing nomophilachy and the paranormative exercise of administrative justice with technical discretion of the executive